EFEKTIVITASILODALAM MENJALANKAN MY-PECTAHUN 2014-2017DITINJAU DARI VARIABEL STRUKTURAL - Prameita Yastini, Made Dwi; Putri, Penny Kurnia; Parameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2019), 2019)
ABSTRACT Myanmar is a small economy country with a high number of child laborers. The chronic problem of child labor gain major concern from ILO. As a United Nations agency, ILO established a program entitled "Myanmar Programme on the Elimination of Child Labour (My-PEC)". Through My-PEC, ILO is striving to reduce child labor in Myanmar through gathering national-level data on child labor, raising awareness, developing capacity, and forming policies according to international standards. By using descriptive qualitative method, this research aims to describe the effectiveness of ILO as an international organization in implementing My-PEC in 2014-2017.The frameworksused in this research are of the effectiveness of international organizations to answer the effectiveness of ILO in implementing My-PEC in 2014-2017.   Keywords: Myanmar, Child Labour, Effectiveness of International Organizations, ILO